New human CD22/siglec-2 ligands with a triazole glycoside - Prescher, Horst; Brossmer, Reinhard (ChemBioChem, 2017)
CD22 is a member of the Siglec family. Considerable attention has been drawn to the design and synthesis of new Siglec ligands to explore target biology and innovative therapies. In particular, CD22-ligand-targeted nanoparticles with therapeutic functions have proved successful in preclinical settings for blood cancers, autoimmune diseases, and tolerance induction. Here we report the design, synthesis and affinity evaluation of a new class of Siglec ligands: namely sialic acid derivatives with a triazole moiety replacing the natural glycoside oxygen atom. In addition, we describe important and surprising differences in binding to CD22 expressed at the cell surface for compounds with distinct valences. The new class of compounds might serve as a template for the design of ligands for other members of the Siglec family and next-generation CD22-ligand-based targeted therapies.
Gesehen am 24.09.2018